Motivasi Sebagai Mediasi Gaya Kepemimpinan dan Kompensasi Pada Kinerja Karyawan PT BahasakuInggris - Wahyuni Trisnaning; Hery Purnomo; Subagyo Subagyo (Universitas Serang Raya, 2022)
This research aims to find out the meaning of leadership style and compensation on the performance of employees of PT BahasakuInggris with motivation as a mediation variable. This type of research is quantitatively correlational, using a saturated sample of all permanent employees of the teacher division of 50 people. Data collection methods use questionnaires. Data analysis uses path analysis through IBM SPSS Statistic 23 software as well as sobel tests. The study found that leadership styles and motivations have meaning to performance, but not to compensation. Leadership style has no meaning to motivation, but compensation has meaning to motivation. Motivation cannot be a mediation of leadership style and compensation on the performance of PT BahasakuInggris. Keywords: Motivation; Leadership; Compensation; Performance; BahasakuInggris.